THE DYNAMICS OF PALM OIL WORKERS' COMMUNITIES: A LITERATURE REVIEW ON THE RELATIONSHIP BETWEEN WORKING CONDITIONS, ECONOMIC ACCESS, AND LIVELIHOOD SUSTAINABILITY STRATEGIES IN INDONESIAN PLANTATION AREAS - Gunawan Widjaja (Adisam Publisher, 2025)
This study examines the dynamics of the lives of palm oil workers in Indonesian plantation areas, focusing on the relationship between working conditions, economic access, and livelihood sustainability strategies. Through a systematic literature review, the study identifies that uncertain working conditions and high occupational health risks limit income stability and workers' access to formal financial services. These constraints encourage palm oil workers to adopt adaptive strategies that include livelihood diversification, utilisation of community social capital, and investment in children's education as efforts to maintain livelihood sustainability. This study emphasises the need for integrated interventions from the government, companies, and community institutions to improve working conditions and expand inclusive economic access, as well as to support sustainable and equitable livelihood strategies. These findings serve as an important foundation for efforts to holistically improve the welfare of palm oil workers.